Global whole lithosphere isostasy : implications for surface elevations, structure, strength, and densities of the continental lithosphere - Lamb, Simon (2021)
The observed variations in the thickness of the conductive lithosphere, derived from surface wave studies, have a first‐order control on the elevation of the continents, in addition to variations in the thickness of the crust—this defines whole lithosphere isostasy (WLI). Negative buoyancy of the mantle lithosphere counters the positive buoyancy of the crust, and together, their respective thicknesses and density contrasts determine elevation of the continents both in their interiors and at their edges. The average density contrasts for lithospheric mantle with crust and with asthenosphere are typically 300 to 550 and 20 to 40 kg m−3, respectively, with a ratio 10 to 16, suggesting moderate average depletion of lithospheric mantle. We show that a crustal model for Antarctica, assuming WLI and using these density contrasts, provides a close fit to estimates of crustal thickness from surface wave tomography and gravity observations. We use a global model of WLI as a framework to assess factors controlling topography, showing that plausible regional variations in crustal and mantle densities, together with uncertainties in the crustal and conductive lithospheric thicknesses, are sufficient to account for global elevations without invoking dynamic topography greater than a few hundred meters. Estimates of elastic thickness Te in the continents are typically 25–50% of the thickness of the conductive lithosphere, indicating that the mantle part supports some of the elastic strength of the lithosphere.